2008
DOI: 10.1016/j.molmed.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic effects of statin therapy: molecular mechanisms and clinical results

Abstract: Statins inhibit the enzyme 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase, which is required for cholesterol biosynthesis, and are beneficial in the primary and secondary prevention of cardiovascular disease. Most of the benefits of statin therapy are owing to the lowering of serum cholesterol levels. However, by inhibiting HMG-CoA reductase, statins can also inhibit the synthesis of isoprenoids, which are important lipid attachments for intracellular signaling molecules, such as Rho, Rac and Cdc42.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
401
1
12

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 537 publications
(420 citation statements)
references
References 104 publications
6
401
1
12
Order By: Relevance
“…Indeed, modus-operandi of the statin medication is to trick the metabolism into destroying free LDL particles in serum instead of recycling cholesterol in them. [74] Incidentally, this explains why statins are especially effective at early stages of CVD. Therefore, both LDL and TC are expected to fall.…”
Section: Atherogenic Indexmentioning
confidence: 99%
“…Indeed, modus-operandi of the statin medication is to trick the metabolism into destroying free LDL particles in serum instead of recycling cholesterol in them. [74] Incidentally, this explains why statins are especially effective at early stages of CVD. Therefore, both LDL and TC are expected to fall.…”
Section: Atherogenic Indexmentioning
confidence: 99%
“…Statins are widely prescribed drugs for the treatment of hypercholesterolemia and act to reduce plasma cholesterol levels by inhibiting the rate-limiting enzyme in the cholesterol biosynthetic pathway, 3-hydroxy-3-methy-lglutaryl-CoA reductase. In addition to the cholesterol lowering effect, statins have many pleiotropic effects, such as reducing Aβ production, suppressing inflammatory responses, protecting neurons from excitotoxins, apoptosis, and oxidative stresses, and promoting synaptogenesis [16][17][18][19] . In particular, statins have been linked to the reduced prevalence of AD in statin-prescribed populations [20,21] , the improved cognition in normo-cholesterolemic patients [22] , and the slowed cognitive decline in mild-to-moderate AD patients [23] .…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis by Wong et al also showed that statins have preventive effects on AD [13] . Evidence from cell culture experiments and animal studies has suggested that statins have many pleiotropic effects, such as reducing Aβ production, suppressing inflammatory responses, protecting neurons from Aβ-induced neurotoxicity, apoptosis and oxidative stress, and promoting synaptogenesis [14][15][16][17] . Recently, a transgenic mouse model of tauopathy showed a reduction in NFTs in response to statin treatment in both early and late stages of disease progression [18] .…”
Section: Introductionmentioning
confidence: 99%